Development of benzoxazole deoxybenzoin oxime and acyloxylamine derivatives targeting innate immune sensors and xanthine oxidase for treatment of gout. Issue 8 (1st May 2018) - Huang, Jun; Zhou, Zehao; Zhou, Mengze; Miao, Mingxing; Li, Huanqiu; Hu, Qinghua
Graphical abstract: Abstract: Both the inhibition of inflammatory flares and the treatment of hyperuricemia itself are included in the management of gout. Extending our efforts to development of gout therapy, two series of benzoxazole deoxybenzoin oxime derivatives as inhibitors of innate immune sensors and xanthine oxidase (XOD) were discovered in improving hyperuricemia and acute gouty arthritis. In vitro studies revealed that most compounds not only suppressed XOD activity, but blocked activations of NOD-like receptor (NLRP3) inflammasome and Toll-like receptor 4 (TLR4) signaling pathway. More importantly, ( E )-1-(6-methoxybenzo[ d ]oxazol-2-yl)-2-(4-methoxyphenyl)ethanone oxime (5d ) exhibited anti-hyperuricemic and anti-acute gouty arthritis activities through regulating XOD, NLRP3 and TLR4. Compound 5d may serve as a tool compound for further design of anti-gout drugs targeting both innate immune sensors and XOD.